EMERGÊNCIA E CRESCIMENTO INICIAL DE MAMONA EM CONDIÇÕES DE DEFICIÊNCIA HÍDRICA - DOURADINHO, Gabriel Zanuto; OLIVEIRA, Camilla Paulino de; BORTOLAZZO, Guilherme; SILVA, Celi Santana; ZOZ, Tiago (ANAIS DO ENIC, 2018)
-